2017
DOI: 10.7554/elife.30697
|View full text |Cite
|
Sign up to set email alerts
|

Aversive stimuli drive hypothalamus-to-habenula excitation to promote escape behavior

Abstract: A sudden aversive event produces escape behaviors, an innate response essential for survival in virtually all-animal species. Nuclei including the lateral habenula (LHb), the lateral hypothalamus (LH), and the midbrain are not only reciprocally connected, but also respond to negative events contributing to goal-directed behaviors. However, whether aversion encoding requires these neural circuits to ultimately prompt escape behaviors remains unclear. We observe that aversive stimuli, including foot-shocks, exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
154
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(161 citation statements)
references
References 43 publications
7
154
0
Order By: Relevance
“…Here we provide evidence for the existence of two neuronal populations in the LHb, both encoding aversive stimuli in an opposite fashion, namely via excitation or inhibition. Indeed, in this study, alongside with a previously characterized aversion‐excited population (Lecca et al., ; Matsumoto & Hikosaka, ; Trusel et al., ), we describe a territorially segregated, glutamate‐containing LHb neuronal subtype inhibited by Fs. Interestingly, in the anaesthetized mouse, these Fs‐inhibited cells preferentially fire more regularly and at a higher frequency (with a relatively rare occurrence of spikes in burst) compared to Fs‐excited neurons.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Here we provide evidence for the existence of two neuronal populations in the LHb, both encoding aversive stimuli in an opposite fashion, namely via excitation or inhibition. Indeed, in this study, alongside with a previously characterized aversion‐excited population (Lecca et al., ; Matsumoto & Hikosaka, ; Trusel et al., ), we describe a territorially segregated, glutamate‐containing LHb neuronal subtype inhibited by Fs. Interestingly, in the anaesthetized mouse, these Fs‐inhibited cells preferentially fire more regularly and at a higher frequency (with a relatively rare occurrence of spikes in burst) compared to Fs‐excited neurons.…”
Section: Discussionsupporting
confidence: 66%
“…Interestingly, mapping the position of recorded neurons using post hoc histological analysis revealed that Fs‐inhibited cells were mainly located in the medial portion of the LHb (Figure e). In contrast, Fs‐excited neurons were found throughout the LHb without any apparent territorial preference (Lecca et al., ). Both inhibitory and excitatory responses to Fs shared similar properties including latency (Fs‐excited vs. Fs‐inhibited: 70.6 ± 8.38 ms vs. 77.08 ± 15.47 ms; Mann‐Whitney test, U = 593.5, p = 0.471) and duration (Fs‐excited vs. Fs‐inhibited: 145.2 ± 15.12 ms vs. 137.9 ± 16.98 ms; Mann‐Whitney test, U = 591, p = 0.46) of the response (Figure f).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations